2021
DOI: 10.1523/jneurosci.1888-20.2020
|View full text |Cite
|
Sign up to set email alerts
|

Roles of the Default Mode and Multiple-Demand Networks in Naturalistic versus Symbolic Decisions

Abstract: The default mode network (DMN) is often associated with representing semantic, social, and situational content of contexts and episodes. The DMN may therefore be important for contextual decision-making, through representing situational constraints and simulating common courses of events. Most decision-making paradigms, however, use symbolic stimuli and instead implicate cognitive control regions, such as the multiple demand (MD) system. This fMRI study aimed to contrast the brain mechanisms underlying decisio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 47 publications
1
16
1
Order By: Relevance
“…Given that the self condition, like rest, promotes an internal mental focus, this suggests that BF responses generally tracked the switch between internal and external cognitive states. While DMN cortical regions also exhibited switching responses during the rest to external task transitions, consistent with other recent studies (Crittenden et al 2015;Smith et al 2018Smith et al , 2021, they were less prominent than the BF's response and were more broadly defined by activity suppression. In the rodent study by Nair et al (2018), the transition between rest and external task states, especially the reengagement of DMN cortical activity during rest, was causally attributed to BF function.…”
Section: Discussionsupporting
confidence: 89%
“…Given that the self condition, like rest, promotes an internal mental focus, this suggests that BF responses generally tracked the switch between internal and external cognitive states. While DMN cortical regions also exhibited switching responses during the rest to external task transitions, consistent with other recent studies (Crittenden et al 2015;Smith et al 2018Smith et al , 2021, they were less prominent than the BF's response and were more broadly defined by activity suppression. In the rodent study by Nair et al (2018), the transition between rest and external task states, especially the reengagement of DMN cortical activity during rest, was causally attributed to BF function.…”
Section: Discussionsupporting
confidence: 89%
“…Results tend to support a proposal by which this involvement in tasks largely occurs when they benefit from memory guidance (Crittenden et al, 2015;Konishi et al, 2015;Murphy et al, 2019Murphy et al, , 2018Sormaz et al, 2018;Spreng et al, 2014;Vatansever et al, 2017). Some HOLISTIC Model 37 have even suggested that those memories take the form of contextually relevant situation models (Chen et al, 2017;Keidel et al, 2018;Ranganath and Ritchey, 2012;Smith et al, 2021Smith et al, , 2018.…”
Section: Holistic Model 36mentioning
confidence: 64%
“…The specialization of such a network in the active controlled integration of exteroceptive information may lead to the provision of relevant information in working memory (Parr & Friston, 2017) in order to construct an internal representation of the external world that is relevant to the individual at a specific time. Second, the fronto-parietal network [FPN; close to the Multiple Demand Network (MDN): Smith et al, 2021, or to the Central Executive Network (CEN); Doucet et al, 2019] is a network involved in all processing requiring controlled attention directed toward internal cues and goals. This network operates for endogenous and top-down attentional redirection (Perrone-Bertolotti et al, 2020) and is engaged in verbal working memory and “fluid” cognition (Assem et al, 2020).…”
Section: Discussionmentioning
confidence: 99%